2014
DOI: 10.1007/978-3-642-45195-9_14
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of Prostate Cancer with the Polyamine Synthesis Inhibitor Difluoromethylornithine

Abstract: In vitro and in vivo preclinical results suggest that inhibition of polyamine synthesis inhibits the progression of prostate cancer. These findings has led to two clinical trials in patients at risk for invasive prostate cancer with difluoromethylornithine which specifically and irreversibly inhibits ornithine decarboxylase which catalyses the conversion of ornithine to putrescine the rate limiting step in polyamines synthesis. We have conducted a phase IIa one month and placebo randomized phase IIb 12 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…While the mechanism by which MR inhibits prostate cancer development is not known, evidence suggests that MR may work by inhibiting prostate cancer cell proliferation, inhibiting the insulin/IGF-1 axis, or by reducing polyamine synthesis [82]. The cells of the prostate produce high levels of polyamines and inhibition of polyamine synthesis is effective at suppressing tumor growth in prostate cancer [91]. Given the dependence of polyamine synthesis on methionine, the polyamine biosynthetic pathway may be a primary target of MR in prevention and/or treatment of prostate cancer.…”
Section: Methionine Restriction and Prostate Cancermentioning
confidence: 99%
“…While the mechanism by which MR inhibits prostate cancer development is not known, evidence suggests that MR may work by inhibiting prostate cancer cell proliferation, inhibiting the insulin/IGF-1 axis, or by reducing polyamine synthesis [82]. The cells of the prostate produce high levels of polyamines and inhibition of polyamine synthesis is effective at suppressing tumor growth in prostate cancer [91]. Given the dependence of polyamine synthesis on methionine, the polyamine biosynthetic pathway may be a primary target of MR in prevention and/or treatment of prostate cancer.…”
Section: Methionine Restriction and Prostate Cancermentioning
confidence: 99%
“…By contrary, the mean uorescent intensity of A549 cells incubated with SPD-DOX-NPs was increased signicantly (P < 0.05) aer DFMO preconditioning for 24 h. In fact, DFMO was as a suicide inhibitor of ornithine decarboxylase (ODC), one of the key enzymes involved in polyamine biosynthesis. 35,36 The PTS activity of cancer cells was usually upregulated to replenish depleted intracellular polyamine pools, 37,38 leading more SPD-DOX-NPs transported into cells. However, the internalization efficiency reduced slightly due to the affection of cell viability when the amount of DFMO over 50 mM (Fig.…”
Section: Pretreatment With Spd or Dfmomentioning
confidence: 99%
“…All together these observations validate the polyamine pathway as chemopreventive and chemotherapeutic for PCa. Several trials have focused on targeting the polyamine pathway as a strategy for chemoprevention in patients at risk for aggressive PCa using difluoromethylornithine (DFMO), an inhibitor of ODC [238,239]. The results of those trials indicated that DMFO treatment results in decreased levels of putrescine, decreased rate of prostate growth, and a trend towards decreased PSA doubling time.…”
Section: Therapeutic Approaches To Prostate Cancer: Targeting the mentioning
confidence: 99%